2002
DOI: 10.1289/ehp.02110165
|View full text |Cite
|
Sign up to set email alerts
|

Association of the blood/air partition coefficient of 1,3-butadiene with blood lipids and albumin.

Abstract: Pulmonary gas uptake is a function of the blood solubility of a vapor, indicated by the blood/air partition coefficient. We hypothesized that blood lipid compositions are associated with the blood/air partition coefficients of lipophilic toxic vapors such as 1,3-butadiene. Our goal was to investigate cross-sectional and longitudinal relationships of blood triglycerides, total cholesterol, and albumin to the blood/air partition coefficient of butadiene. We collected blood samples from 24 subjects at three time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Age does not appear to have a large effect on metabolic rate; although, older subjects have slightly higher mean level of fraction ofblood flow to fat tissue, and higher level of air/blood partition coefficient. Lin et al (2002) also reported that air/blood partition coefficient, a major factor in the uptake of BD was significantly associated with age. However, the younger group (less than 30 years) here had slightly higher K met and percent of BD metabolized at steady state, although the difference was not significant.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Age does not appear to have a large effect on metabolic rate; although, older subjects have slightly higher mean level of fraction ofblood flow to fat tissue, and higher level of air/blood partition coefficient. Lin et al (2002) also reported that air/blood partition coefficient, a major factor in the uptake of BD was significantly associated with age. However, the younger group (less than 30 years) here had slightly higher K met and percent of BD metabolized at steady state, although the difference was not significant.…”
Section: Discussionmentioning
confidence: 90%
“…We have described an extension of the use of a Bayesian hierarchical physiologicallybased pharmacokinetic model to estimate the metabolic rate of BD in human subjects, which was reported earlier by Lin et al (2002) and Mezzetti et al (2003). Our question of interest here is the estimation of another quantity (percent BD metabolized at steady-state) that is equivalent to the metabolic rate, and whether this quantity differs between the sexes, race and age groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although inter-species differences in blood composition are relatively small (Nelson 1972;Nelson 1967), partition coefficients have been found to vary with changes in hematocrit and blood lipids (Fiserova-Bergerova 1983;Lin et al 2002). There is considerable variation in reported blood-air partition coefficients of a chemical between studies as indicated by 90% confidence intervals in Figure 1.…”
Section: Blood-air Partition Coefficientsmentioning
confidence: 98%
“…One of the most important properties in determining the respiratory kinetics of volatile chemicals in mammals is the blood-air partition coefficient (Lin et al 2002). In bioaccumulation modeling, it is common practice to assume that chemical affinity for tissues is a function of the octanol-water partition coefficient of the chemical and the fat content of the organism.…”
Section: Introductionmentioning
confidence: 99%